Conferred resistance to Botrytis cinerea in Lilium by overexpression of the RCH10 chitinase gene - Núñez de Cáceres González, Francisco; Davey, Michael R.; Cancho Sánchez, Ester; Wilson, Zoe A. (Springer, 2015)
The production of ornamentals is an important global industry, with Lilium being one of the six major bulb crops in the world. The international trade in ornamentals is in the order of £60-75 billion and is expected to increase worldwide by 2-4 % per annum. The continued success of the floriculture industry depends on the introduction of new species/cultivars with major alterations in key agronomic characteristics, such as resistance to pathogens. Fungal diseases are the cause of reduced yields and marketable quality of cultivated plants, including ornamental species. The fungal pathogen Botrytis causes extreme economic losses to a wide range of crop species, including ornamentals such as Lilium. Agrobacterium-mediated transformation was used to develop Lilium oriental cv. ‘Star Gazer’ plants that ectopically overexpress the Rice Chitinase 10 gene (RCH10), under control of the CaMV35S promoter. Levels of conferred resistance linked to chitinase expression were evaluated by infection with Botrytis cinerea; sporulation was reduced in an in vitro assay and the relative expression of the RCH10 gene was determined by quantitative Reverse-Transcriptase PCR. The extent of resistance to Botrytis, compared to that of the wild type plants, showed a direct correlation with the level of chitinase gene expression. Transgenic plants grown to flowering showed no detrimental phenotypic effects associated with transgene expression. This is the first report of Lilium plants with resistance to Botrytis cinerea generated by a transgenic approach.